Flood Water Level Mapping and Prediction Due to Dam Failures. Issue 1 (July 2016) - Musa, S; Adnan, M S; Ahmad, N A; Ayob, S
Abstract: Sembrong dam has undergone overflow failure. Flooding has been reported to hit the town, covering an area of up to Parit Raja, located in the district of Batu Pahat. This study aims to identify the areas that will be affected by flood in the event of a dam failure in Sembrong Dam, Kluang, Johor at a maximum level. To grasp the extent, the flood inundation maps have been generated by using the InfoWorks ICM and GIS software. By using these maps, information such as the depth and extent of floods can be identified the main ares flooded. The flood map was created starting with the collection of relevant data such as measuring the depth of the river and a maximum flow rate for Sembrong Dam. The data were obtained from the Drainage and Irrigation Department Malaysia and the Department of Survey and Mapping and HLA Associates Sdn. Bhd. Then, the data were analyzed according to the established Info Works ICM method. The results found that the flooded area were listed at Sri Lalang, Parit Sagil, Parit Sonto, Sri Paya, Parit Raja, Parit Sempadan, Talang Bunut, Asam Bubok, Tanjung Sembrong, Sungai Rambut and Parit Haji Talib. Flood depth obtained for the related area started from 0.5 m up to 1.2 m. As a conclusion, the flood emanating from this study include the area around the town of Ayer Hitam up to Parit Raja approximately of more than 20 km distance. This may give bad implication to residents around these areas. In future studies, other rivers such as Sungai Batu Pahat should be considered for this study to predict and reduce the yearly flood victims for this area.